THE APPLICATION OF THE BOUNDARY ELEMENT METHOD TO SOLVE VISCOUS FLOW PROBLEMS BASED ON PRIMITIVE VARIABLES FORMULATION - Santos, M. F. C. L.; Barbosa, J. R.; Carneiro, H. F. F. M. (Revista de Engenharia Térmica, 2004)
The boundary element method is applied to the solution of incompressible fluid flow problems governed by the continuity and Navier-Stokes equations. The differential equations are transformed into integral equations. Indication of the transformation is given in detail. Application to simple flow cases such as the driven cavity and forward facing step is presented. Convergence difficulties are indicated, which have limited the applications to flows of low Reynolds numbers..